2021
DOI: 10.1111/adj.12888
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic properties of glass‐ionomer cements: Their application to orthodontic treatment

Abstract: Fluoride has been shown to be an effective agent in the prevention of caries during orthodontic treatment. Resin‐modified glass‐ionomer cements possess therapeutic anticariogenic properties acting as a fluoride reservoir and releasing fluoride into the environment, particularly at low pH where there is a threat of enamel demineralisation and white spot lesions (WSL’s). Patient compliance to instructions in standard oral hygiene measures limits the success of caries prevention and the routine use of glass‐ionom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 62 publications
0
6
0
Order By: Relevance
“…Because the monomers responsible for etching are also responsible for bonding, the depth of the demineralized zone corresponds to the penetration depth of the polymerized adhesive. As a consequence, there are no problems with insufficient penetration depth, which improves the quality of the bond and benefits the long-term treatment process [ 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Because the monomers responsible for etching are also responsible for bonding, the depth of the demineralized zone corresponds to the penetration depth of the polymerized adhesive. As a consequence, there are no problems with insufficient penetration depth, which improves the quality of the bond and benefits the long-term treatment process [ 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Despite the doubts, there is evidence of effectiveness in some clinical applications, at least. Studies have shown that resin-modified glass-ionomers are good adhesives for orthodontic brackets [ 93 , 94 ] and, in particular, the problem of white spot lesions adjacent to cemented brackets that arise from enamel demineralization with certain adhesives, do not occur with glass-ionomers. Studies have also shown that resin-modified glass-ionomers as bonding agents for orthodontic brackets are associated with reduced enamel demineralization [ 95 ].…”
Section: Methodsmentioning
confidence: 99%
“…For this reason, the development of these materials has led to the introduction of RMGICs in orthodontics. These materials, with their improved mechanical properties, offer several advantages compared with composite resins [ 14 17 ]: prevention of white spot lesions [ 18 ] by fluoride release [ 19 ] and cariogenic bacterial growth inhibition [ 20 ], reduction in the risk of iatrogenic damage to the enamel during debonding [ 20 , 21 ], preservation of weakened enamel (molar incisor hypomineralization, amelogenesis imperfecta, etc.) [ 22 ] and tolerance to humidity [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%